The Journal of Turhish Librariarıship, 1987-2001 - Yaşar Tonta (Türk Kütüphaneciliği)
The journal of Türk Kütüphaneciliği (Turkish Librarianship) has been published since 1987. A continuation ofthe Türk Kütüphaneciler Derneği Bülteni (Bulletin of the Turkish Librarians’ Association) that was published between 1952 and 1986, Türk Kütüphaneciliği became a refereed journal in 1995. Based on a revi- ew of238 articles published in the journal between 1987-2001 (135 ofwhich we- re published before it became refereed, 103 after), this study compares some bib- liometric features (number ofpages in each issue, the length of articles, authors, topics, citations, ete.) of articles that w ere published before the journal became refereed with these after. The average number ofpages in each issue inereased 81% after the journal became refereed. The average length of an article inereased 75% (from 8 pages to 14 pages). The number of citations per article inereased 65% (from 11 citations to 17 citations). The percentage of articles having abstracts in Turkish and English inereased from 24% to 96%. Articles were writ- .ten by 94 dijferent authors representing 42 institutions. Overwhelming majority of articles were written by a single author. Researchers affiliated with the depart- ments of librarianship have authored the majority of articles. More than 20% of articles that appeared in the journal are on libraries (ineluding public, academic, and special libraries), followed by 12% on information retrieval and bibliograp- hic control (cataloging and classification), and 8% on information technology and library automation. More than half (53%) of ali citations (3204) werefor bo- oks while 42% for journals and 5% for “other publications” (e.g., unpublished manuseripts, web sites, among others). Türk Kütüphaneciler Demeği Bülteni, Türk Kütüphaneciliği, Resmî Gazete (Turkish Official Gazette), Library Trends, Journal of the American Society for information Science, information Technology and Libraries and College & Research Libraries are among the most frequ- ently cited journals. Majority of citations were for articles appeared in afew co- re journals, whichfıts Bradford’s Law of Scattering (1934). The problems facing Türk Kütüphaneciliği are also discussed along with some recommendations.